Migration of Oxidized Cellulose to the Ventricle as a Complication of Endoscopic Third Ventriculostomy: A Case Report - da Silva, Aldo J. F.; Fortes, Thiago; Bomfim, Rodrigo C.; Bomfim Filho, Ângelo M. S. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Endoscopic third ventriculostomy (ETV) is an increasingly common neurosurgical procedure. Hemostatic agentes (porcine gelatin and oxidized cellulose) are normally placed to plug the cortical hole after ETV to avoid cerebral spinal fluid leakage, subdural hygroma, and hemorrhage. Here we report the case of a 6-year-old boy with hydrocephalus who underwent ETV and which oxidized cellulose was placed to plug the cortical hole. Magnetic resonance imaging of the head performed 3 months after the procedure showed the presence of oxidized cellulose in the ventricle. After an unsuccessful attempt to remove the cellulose, it was decided that the patient should be kept under observation. Two years later, the child is in good health and without any complaints. Hemostatic agents (especially oxidized cellulose) used on the cortical hole after ETV can migrate to the ventricle and compromise the procedure. Follow-up should be performed for such patients, and the main focus should be on not causing further injury.
Keywords: endoscopy; cellulose; leakage; hydrocephalus